The development of Alexander Bondarko’s ideas in the aspect of grammar of estimation theory - Khaliman, Oxana (Przegląd Wschodnioeuropejski, 2018)
The study of the functional particularity of grammatical units allowed to pay attention to their pragmatic importance in the discursive practice and communication. Based on the principles of linguistic functionalism, which is a basis of active type grammar, it is necessary to continue the study of grammatical units as one of the means of expressing evaluation in relation to their structural peculiarities with the communicative process. A. Bondarko is one of the founders of functional grammar. In his works he has created a systemic-functional description on the Russian grammatical system. Principles of the development of a dynamic aspect of the grammatical units functioning in the interaction with elements of different language levels are one of the postulates which underlie in the description of the expression of evaluative meaning by grammatical units, the principles of grammar of estimation. The article enlightens the principles of the theory of functional grammar, grammar of active type, that concern the problem of creation of grammar of estimation as a complex description of grammatical means for expressing estimation meanings; A. Bondarko’s ideas of functional grammar that are significant for the theory of grammar of estimation are described in the article.